2014
DOI: 10.1259/dmfr.20130273
|View full text |Cite
|
Sign up to set email alerts
|

Regional 3D superimposition to assess temporomandibular joint condylar morphology

Abstract: Objectives: To investigate the reliability of regional three-dimensional registration and superimposition methods for assessment of temporomandibular joint condylar morphology across subjects and longitudinally. Methods: The sample consisted of cone beam CT scans of 36 patients. The across-subject comparisons included 12 controls, mean age 41.3 ± 12.0 years, and 12 patients with temporomandibular joint osteoarthritis, mean age 41.3 ± 14.7 years. The individual longitudinal assessments included 12 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 45 publications
0
42
0
5
Order By: Relevance
“…Twenty-five surface points were selected on each condyle by one observer at corresponding (homologous) areas to closely approximate the various anatomic regions of all individuals who present marked morphological variability: 4 points evenly spaced along the superior surface of the sigmoid notch, 4 on the medial and lateral portions of the ramus adjacent to the sigmoid notch, 3 along the posterior neck of the condyle, 3 on the medial and 3 on the lateral portion of the condylar neck, and on the medial, lateral, anterior, and posterior extremes of the condylar head (Figure 2A). 18 …”
Section: Methodsmentioning
confidence: 99%
“…Twenty-five surface points were selected on each condyle by one observer at corresponding (homologous) areas to closely approximate the various anatomic regions of all individuals who present marked morphological variability: 4 points evenly spaced along the superior surface of the sigmoid notch, 4 on the medial and lateral portions of the ramus adjacent to the sigmoid notch, 3 along the posterior neck of the condyle, 3 on the medial and 3 on the lateral portion of the condylar neck, and on the medial, lateral, anterior, and posterior extremes of the condylar head (Figure 2A). 18 …”
Section: Methodsmentioning
confidence: 99%
“…92 The reliability of regional 3D registration and superimposition methods for the assessment of mandibular condyle morphology, across subjects and longitudinally, has been found to be acceptable. 93 The authors claim that subtle bony differences in 3D condylar morphology can be quantified. The method was applied to assess changes in condylar 3D morphology in patients who underwent maxillomandibular advancement with and without simultaneous disc repositioning.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Based on the cranial base registrations, it is possible to quantify the skeletal displacements of both the maxilla and mandible relative to the anterior cranial base used as a stable reference structure. Recently, Schilling et al 15 suggested a regional superimposition method to assess dental changes and subtle bone remodeling within the mandible that considers the symphysis as a stable reference structure. To date, no study in the literature described the 3D voxel-based regional superimposition method for the maxilla.…”
Section: Introductionmentioning
confidence: 99%